Amyotrophic lateral sclerosis caregiver burden and patients' quality of life during COVID-19 pandemic. Issue 1 (2nd January 2022) - Giusiano, Silvia; Peotta, Laura; Iazzolino, Barbara; Mastro, Enza; Arcari, Martina; Palumbo, Francesca; Torrieri, Maria Claudia; Bombaci, Alessandro; Grassano, Maurizio; Cabras, Sara; Di Pede, Francesca; DeMattei, Filippo; et al.
Abstract: Objective: To assess patients Quality of life (QoL) and the burden of their caregivers during Covid-19 pandemic and specifically the impact of two-month lockdown period. Methods : In April 2020, a total of 60 patients and 59 caregivers were administered by phone scales assessing patients' QoL (McGill QoL Questionnaire), general health status (EQ-5D-5L), and caregiver burden (Zarit Burden Interview). The administration was repeated one month after the end of lockdown measures, with the addition of a qualitative questionnaire (COVID-QoL Questionnaire) exploring family reorganization and personal perception of lock down. Results : QoL and perceived health status did not worsen during lockdown, while caregiver burden increased ( p  = 0.01). Patient's QoL and caregiver burden were inversely correlated at T1 (ZBI total score mildly correlated with Mc Gill existential subscore, p  = 0.02, rho = 0.30 and with Mc Gill total score, p  = 0.05, rho = 0.265). No significant correlations were found at T2. According to the COVID-QoL questionnaire, caregivers perceived lower family help compared to patients ( p  < 0.001). Conclusions : Restricted measures of lockdown period during COVID-19 pandemic did not result in a significant reduction of QoL in our cohort of ALS patients, while caregiver burden significantly increased. ALS motor impairment may have played a role in the unchanged life conditions of patients. Instead, the restriction of family help for primary caregivers could be responsible of their increased burden, reflecting the importance of a wide social support in the management of this clinical condition.